KNOWLEDGE AND PRACTICE ON DISINFECTION, STERILIZATION MEDICAL INSTRUMENTS OF HEALTH STAFFS AT THE NATIONAL EYES HOSPITAL, IN 2021 (Vietnam Journal of Community Medicine, 2022)
Background: Reusing medical instruments in care and treatment at medical examination andtreatment facilities is a routine practice. This reuse process, if not strictly followed from cleaning todisinfection and sterilization, can have serious consequences, affecting the quality of examinationand treatment of patients.Objectives: Describe the knowledge and practice on disinfection, sterilization medical instrumentsof medical staff at the National Eye Hospital and analyze some related factors.Methods: Cross-sectional survey, quantitative research.Results: This study collected information from 323 health workers (NVYT), National Eye Hospitalthrough questionnaires and observation using checklists. The research results show that the knowledgeand practice on disinfection, sterilization medical instruments in the control of hospital-acquiredinfections of health workers is quite good.Conclusion: The rate of health workers with knowledge on disinfection, sterilization medicalinstruments reached 67,2%. The rate of health workers with practices on on disinfection, sterilizationmedical instruments reached over 80%. There are 4 factors related to knowledge on disinfection,sterilization medical instruments including: age, working position, working time and professionalqualifications. Three factors related to practices on disinfection, sterilization medical instrumentsincluding: Gender, working position and time of training on infection control (p
Keywords: Disinfection, sterilization medical instruments, related factors, health workers.